BAHASA DAN KESUSASTRAAN BALI SEBAGAI PEMBENTUK KARAKTER - I Made Suweta (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2020)
Character education can be integrated in learning on any subject. Learning materialsrelated to norms or values in each subject need to be developed, exported, and attributed to thecontext of daily life. Thus, learning character values is not only on the cognitive level, buttouching on internalization, and the real practice in the lives of daily learners in the community.In this study there are several problems that will be discussed namely: (1) How is the role ofBalinese language in shaping the character? and (2) How is the implementation of charactereducation in Balinese language? Balinese language and literary works have a very importantrole in facing the life of Balinese people who have character in accordance with the purpose ofnational character education. Balinese language is not outdated, does not appreciate the nationallanguage. But this is a Balinese form of character that truly characterizes the Balinese. This isa form of local wisdom that later if still sustainable will have a broader impact on improvingintelligence, benefit in social life, love of ancestral heritage, and will ultimately affect the Theworld of Bali's tourism that features culture and more breadth will scent our beloved countrynamely Indonesia.